PROFIL KETERAMPILAN PSIKOMOTOR MAHASISWA CALON GURU BIOLOGI MELALUI PRAKTIKUM KULTIVASI MIKROORGANISME - Rida Oktorida Khastini; Amalia Sapriati; Mestika Sekarwinahyu (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2017)
AbstractGeneral microbiology course provide comprehensive introduction to fundamental aspects of microbial world so that student gain an insight into theory, practices and able to demonstrate in the term of knowledge skills and values to overcome problem in the environment. Therefore student should have psychomotor skill as well as cognitive. The present study aimed to identify and describe the psychomotor skills of Pre Service Biology Teacher through microorganism cultivation experiment in the laboratoratory. Data were collected from 94 Pre Service Biology Teacher who enrolled General microbiology course in the even semester of academic year 2016-2017 using psychomotor skill observation sheet. Six dimensions observed: perception, set, guided response, mechanism, adaptation and originalation. Findings indicated that student psychomotor skills was categorized as good with the value of 81,2%.